2021
DOI: 10.1186/s40621-021-00338-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related violence trend data challenges & a resource for injury researchers

Abstract: Published works have raised concerns that certain violent behaviors and firearm acquisition have encountered dramatic increases since the onset of COVID-19. While these works provide important preliminary insights, they lack the empirical robustness necessary to inform a targeted societal response. Having the ability to perform the research needed to support evidence-based policy requires that data at national, state and local-levels be accessible and of sufficient quality. While related, robust data sources d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In prior work, fatal shootings matched government records at higher rates (83%) 23 and closely aligned with aggregated government data. 13 It is unknown whether GVA data on fatal shootings display systematic bias (e.g., by victim's race), but if they did, the current study would likely underestimate disparities. Moreover, though the current study's results align with estimates from other sources that homicides increased by approximately 30% during the COVID-19 pandemic, 44 it is possible that GVA data collection procedures have improved over time, in which case using these data to assess longitudinal trends could overestimate the COVID-19-related increase in firearm injuries.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In prior work, fatal shootings matched government records at higher rates (83%) 23 and closely aligned with aggregated government data. 13 It is unknown whether GVA data on fatal shootings display systematic bias (e.g., by victim's race), but if they did, the current study would likely underestimate disparities. Moreover, though the current study's results align with estimates from other sources that homicides increased by approximately 30% during the COVID-19 pandemic, 44 it is possible that GVA data collection procedures have improved over time, in which case using these data to assess longitudinal trends could overestimate the COVID-19-related increase in firearm injuries.…”
Section: Discussionmentioning
confidence: 83%
“…GVA captures fatal shootings with good accuracy: 83% of fatal shootings from 3 cities were accurately represented in GVA data on date, location, and victim age and gender 23 ; in 2018, GVA under-reported fatal shootings by just 2%, compared with government counts. 13 By contrast, GVA only matched 43% of nonfatal shooting incidents in the 3-city study, and no government source exists for nonfatal shootings, leaving important questions about GVA accuracy for nonfatal shootings.…”
Section: Methodsmentioning
confidence: 91%
“…GVA has allowed researchers to conduct analyses of fatal and nonfatal intentional interpersonal shootings on a national level, including studies examining the spike in firearm violence following COVID-19 containment policies. Some prior work has found that the annual counts of homicides in the GVA align closely with federal estimates, yet other work has found that the GVA data contain gaps . To our knowledge, no study has validated event-level counts of GVA incidents, although some studies have shown aggregate area-level counts of the GVA data to be correlated with data provided by police departments and the Centers for Disease Control and Prevention.…”
Section: Introductionmentioning
confidence: 95%